Impact of carotid artery revascularization on cognitive function: a study of symptomatic and asymptomatic cases - Wu, Sensen; Ning, Yachan; Wang, Hui; Pan, Dikang; Guo, Julong; Wang, Cong; Wang, Chunmei; Gu, Yongquan; Guo, Lianrui (Frontiers in Neurology, 2025)
ObjectiveTo investigate and compare changes in cognitive function following revascularization between patients with symptomatic and asymptomatic carotid stenosis.MethodsFrom April 2019 to April 2022, patients carotid artery stenosis who were treated with carotid endarterectomy (CEA) or carotid artery stenting (CAS) were recruited for this study. The Montreal Cognitive Assessment (MoCA) instrument was used to evaluate cognitive function preoperatively and at 3, 6, and 12 months postoperatively. Patients were divided into two groups based on the neurological symptoms, repeated measures ANOVA was used for comparisons.ResultsA total of 89 patients who met the criteria were enrolled and completed 1-year follow-up, divided into symptomatic group (32 patients) and asymptomatic group (57 patients). Baseline data showed no significant differences in clinical characteristics between the two groups. At 3, 6, and 12 months after carotid revascularization, the total MoCA and delayed recall scores for both groups showed significant increases compared to baseline levels. In patients with asymptomatic, attention also showed improvement at 3, 6 months compared to baseline (p < 0.05).ConclusionCarotid revascularization has a positive impact on cognitive function improvement, particularly in delayed recall and attention.